Strategi Segmentasi, Targeting dan Positioning terhadap Keputusan Pembelian Produk pada Mebel Caruban di Pulau Buru - Arman Arman; Rizky Rizky (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to (a) determine the effect of segmentation strategy, targeting strategy and positioning strategy on product purchase decisions for Caruban furniture in Jikubesar Hamlet, Namlea, Buru. The method used is quantitative with cross sectional, ie the process of collecting data on research variables is carried out at one research time. The population in this study are consumers who want to buy and have bought as many as 105 people. Primary data collection was carried out by survey method using a questionnaire (questionnaire). The results showed that the variable segmentation did not have a positive effect on purchasing decisions. Targeting variable has a significant positive effect on purchasing decisions. In other words, it can be said that the increasingly diverse targeting provided by the caruban furniture party will make consumers more interested and loyal. Positioning variable has a significant positive effect on purchasing decisions. In other words, it can be said that the various positioning given by the caruban furniture will make consumers more interested and loyal.